2015
DOI: 10.4103/0972-0707.153073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of technique of sealer agitation on percentage and depth of MTA Fillapex sealer penetration: A comparative in-vitro study

Abstract: Aim:To compare the effect of three root canal sealer activation techniques on percentage and depth of sealer penetration of MTA Fillapex and AH Plus sealers.Materials and Methods:Sixty teeth prepared till F5 ProTaper size were divided into three equal groups on the basis of sealer activation technique (G1: Ultrasonics, G2: Lentulo spiral, and G3: Counter-clockwise rotary motion). Each group was further divided into two equal subgroups on the basis of type of sealer used: AH Plus (Denstply, Konstanz, Germany) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
3
30
0
2
Order By: Relevance
“…In the present study, MTA Fillapex showed higher penetrability values when compared with AH Plus, as confirmed by other studies (6,19). Also, the penetrability of MTA Fillapex and AH Plus was not affected by moisture conditions, showing statistically significant difference (P<0.05).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study, MTA Fillapex showed higher penetrability values when compared with AH Plus, as confirmed by other studies (6,19). Also, the penetrability of MTA Fillapex and AH Plus was not affected by moisture conditions, showing statistically significant difference (P<0.05).…”
Section: Resultssupporting
confidence: 79%
“…However, it was not sufficient to show a statistically significant difference. These results could be justified by the different composition and smaller particle size of MTA Fillapex, which has been correlated to greater flowability compared to AH Plus (19). In addition, this could be related to higher lateral condensation forces or due to the dentin structure in these parts of the roots (20).…”
Section: Resultsmentioning
confidence: 91%
“…Nikhil et al (28) compared the depth of penetration of MTA Fillapex and AH Plus sealers into the dentinal tubules with the use of a confocal laser microscope and reported that MTA Fillapex sealer penetrated deeper into the dentinal tubules. These results do not coincide with the results of the present study or it is better to conclude that although MTA Fillapex exhibits deeper penetration into dentinal tubules, it does not result in better apical seal.…”
Section: Discussionmentioning
confidence: 99%
“…Em análises com infiltração bacteriana, resultados divergentes colocam o MTA Fillapex como semelhante 4 ou inferior ao AH Plus 5 . Em relação à penetração tubular dentinária, testes usando microscopia confocal demonstraram maior penetração do MTA Fillapex quando comparado ao AH Plus 6 . O cimento resinoso AH Plus (De trey-Dentsply, Konstanz, Germany) é um cimento insolúvel aos tecidos e com boa capacidade de selamento apical, o que mantém níveis de infiltração menores em relação a outros materiais como o Epiphany, Apexit e Ketac-Endo 7 .…”
Section: Introductionunclassified
“…O cimento resinoso AH Plus (De trey-Dentsply, Konstanz, Germany) é um cimento insolúvel aos tecidos e com boa capacidade de selamento apical, o que mantém níveis de infiltração menores em relação a outros materiais como o Epiphany, Apexit e Ketac-Endo 7 . É o cimento de eleição em estudos comparativos de infiltração 4,5 e penetração intratubular 6 avaliando cimentos novos, como o MTA Fillapex.…”
Section: Introductionunclassified